(untitled) (Physical Education, Health and Social Sciences, 2026)
Agricultural extension services are essential for eliminating the productivity gap in horticulture crops. However, socioeconomic disparities sometimes limit their effectiveness. This study evaluated the impact of extension services on melon cultivation among 102 farmers from district Lakki Marwat, focusing on the influence of education, tenancy status, and visit frequency on yield outcomes. Using a non-parametric approach, data were analyzed through Pearson Chi-square tests and Spearman’s Rank Correlation (r_s). Descriptive results showed that while 76.47% of farmers were literate, the majority (33%) had only primary education. Furthermore, 56.9% were landowners, while 17.6% were tenants. Regarding service delivery, 72.5% of farmers received extension visits, but the frequency was inconsistent, with 48.6% reporting only "Off & On" contact. Results revealed a significant "service gap," as land owners enjoyed substantially higher access to extension (49%) compared to tenant farmers (5.9%, Chi x2 = 18.42, p < 0.001). Furthermore, a strong, positive correlation was found between the frequency of extension visits and yield improvement (r_s= 0.684**, p < 0.001), indicating that regular technical support is a primary driver of productivity. While agents were effective in transferring pest management knowledge, significant gaps remain in irrigation and sowing support. The study concludes that while extension services are highly effective when delivered, current outreach is skewed toward educated landowners. It is recommended that extension policies be restructured to include mandatory registration of tenant farmers and the implementation of visual-based training to overcome literacy barriers, ensuring equitable agricultural development.